Stable carbon isotope fractionation of chlorinated ethenes by a microbial consortium containing multiple dechlorinating genes. (August 2018) - Liu, Na; Ding, Longzhen; Li, Haijun; Zhang, Pengpeng; Zheng, Jixing; Weng, Chih-Huang
Graphical abstract: Highlights: The Ɛ-carbon of CEs degraded by a microbial consortium were observed. The Ɛ-carbon kept stable under different conditions and community structures. Non-overlapping function dechlorinating genes had no effect on isotope fractionation. Abstract: The study aimed to determine the possible contribution of specific growth conditions and community structures to variable carbon enrichment factors ( Ɛ-carbon ) values for the degradation of chlorinated ethenes (CEs) by a bacterial consortium with multiple dechlorinating genes. Ɛ-carbon values for trichloroethylene, cis -1, 2-dichloroethylene, and vinyl chloride were −7.24% ± 0.59%, −14.6% ± 1.71%, and −21.1% ± 1.14%, respectively, during their degradation by a microbial consortium containing multiple dechlorinating genes including tceA and vcrA . The Ɛ-carbon values of all CEs were not greatly affected by changes in growth conditions and community structures, which directly or indirectly affected reductive dechlorination of CEs by this consortium. Stability analysis provided evidence that the presence of multiple dechlorinating genes within a microbial consortium had little effect on carbon isotope fractionation, as long as the genes have definite, non-overlapping functions.